The impact of the café atmosphere on consumer satisfaction, purchase decisions, and retention - Apriliani, Ernix (Lembaga Riset dan Pengabdian Masyarakat (LRPM) Institut Bisnis Nusantara, 2024)
The purpose of this study is to ascertain how the atmosphere affects consumer satisfaction, repurchase intention, and purchasing decisions. The study's participants were guests of Kopi Nako. Purposive sampling was the method employed, and a total of 251 individuals visited. Using smartPLS software, the data analysis method applies structural equation models. The study's findings demonstrate the considerable impact of atmosphere on decisions about what to buy, how satisfied customers are, and whether or not they make repeat purchases. This study makes a significant contribution to management's understanding of the value of fostering a positive environment in the store to boost customer satisfaction and promote repeat business.